Imaging of common bile duct stones - A Nurman, A Nurman (Universa Medicina, 2009)
The gallbladder serves as the repository for bile produced in the liver. However, bile within the gallbladder may become supersaturated with cholesterol, leading to crystal precipitation and subsequent gallstone formation. Gallstone is one of the most common gastrointestinal diseases in clinical practice. Common bile duct stone may be silent and symptomless; alternatively the stone can cause acute cholangitis with jaundice, pain and fever and acute pancreatitis. Imaging of the gallbladder is typically requested for evaluation of right upper quadrant pain in patients with or without fever and jaundice. Hence,imaging is central to the investigation and diagnoses of choledocholithiasis. There are many options in the field of imaging of choledocholithiasis from a simple to more sophisticated examinations. Ultrasonography (US) has been the traditional modality for evaluating gallbladder disease, primarily owing to its high sensitivity and specificity for both stone disease and gallbladder inflammation. However, US is limited by patient body habitus, with degradation of image quality and anatomic detail in obese individuals. With the advent of faster and more efficient imaging techniques, magnetic resonance (MR) imaging has assumed an increasing role as an adjunct modality for gallbladder imaging. MR imaging allows simultaneous anatomic and physiologic assessment of the gallbladder and biliary tract. Magnetic resonance cholangiopancreatography is excellent for identifying the presence and the level of biliary obstruction. With newer diagnostic imaging technologies emerging, endoscopic retrograde cholangiopancreatography is evolving into a predominantly therapeutic procedure.